17. Evaluation of the EDD-53G diodes for their utilization in vivo dosimetry control during total body irradiation. (December 2017) - Michel, M.; Nigoul, J.M.; Champoudry, J.; Garnier, E.; Gempp, S.
Abstract : Introduction: During total body irradiation (TBI), the control of the dose received by the patient during each fraction of the treatment is necessary. The aim of this study was to verify that the EDD-53G diodes could be used in the TBI conditions and afterward to set up a measurement protocol for in vivo dosimetry during the fractions of treatment. Methods: The diodes used were IBA's EDD-53G (black) diodes with an OmniPro-InViDos supports DPD-12 electrometer. All measurements were made with the patient's treatment conditions for a TBI: gantry at 270°, collimator at 45°, irradiation fields size 40 cm by 40 cm and source-skin distance (SSD) of 303 cm, 333 cm, 373 cm or 403 cm (clinically used SSD). Diode calibration was carried out with diodes placed at the input and the output of a phantom of 20 cm composed of RW3 polystyrene plaque with a FARMER ionization chamber (IBA FC65-P) positioned at mid-thickness. During the evaluation phase of the diodes, repeatability and reproducibility studies were carried out. The diodes angulation influence on the irradiation incidence and the diodes influence on each other were evaluated. A verification of the diode's dose linearity was also carried out. Secondly, thickness correction factors (from 4 cm to 30 cm) were established at the four SSD, taking the patient's different thicknesses compared to the reference conditions into account. Results: In the study of the diodes angulation influence, an anisotropy of the diodes according to their rotation axis was established: relative mean deviation σ average = 1.2% (max deviation of 4%) σ average = 0.3% if the diode is always placed in accordance with the same axis. Therefore, the repeatability and reproducibility studies were carried out taking into account this effect and positioning the diode always at the same angle of incidence with the beam. These two studies yielded the following results: σ average = 0.08% for repeatability (σmax = 1.55%) and σ average = 0.88% for reproducibility (σmax = 0.11%). The diode presence in the vicinity of another did not show influence on the measurement (σ average = 0.09%). The response linearity of the diodes according to the delivered dose has been demonstrated (slope coefficient = 1.000 ± 0.001). For each SSD, a correction factor curve to be applied as a function of the thickness of the phantom was performed. Conclusions: The first results obtained with these diodes were satisfying. Subsequently, an anthropomorphic phantom test is considered to verify the in vivo dosimetry measurement protocol with the diodes.